Additional electrode ceramic channel structure for reducing wall surface energy loss - CAO XIFENG; XIA GUOJUN; WANG YUHANG; ZHAO FANGZHOU; MA HONGNING; KUANG SHILIN; ZENG QUN; WANG YIHAN; RONG WANTING (2025)
The invention discloses an additional electrode ceramic channel structure for reducing energy loss of a wall surface, belongs to the field of Hall thrusters, and aims to solve the problem of energy loss caused by bombardment of a large number of ions near a channel outlet position to the wall surface when the conventional Hall thruster works. According to the scheme, a ceramic channel is an annular channel with an upper opening, circumferential cutting grooves are formed in the opposite positions of the inner ring wall face and the outer ring wall face of a channel outlet respectively, and an inner ring additional metal electrode and an outer ring additional metal electrode are embedded in the two circumferential cutting grooves respectively; each circumferential cutting groove is communicated with the outside through two symmetrical radial through holes; the inner electrode positive conductive column and the inner electrode negative conductive column are respectively inserted into two radial through holes sy